(untitled) (Ustozlar uchun, 2025)
The development of multimedia electronic textbooks plays a crucial role in enhancing the effectiveness of English language teaching. This article explores the potential of multimedia resources—such as interactive videos, audio materials, animations, and online platforms—in creating a more engaging and efficient learning environment for students. The integration of multimedia tools allows learners to improve listening, speaking, reading, and writing skills more effectively by providing authentic contexts and visualized language input. Furthermore, it supports teachers by offering ready-made resources, reducing lesson preparation time, and promoting differentiated learning approaches. The research also highlights the necessity of teacher training and digital literacy development to ensure proper implementation of electronic textbooks in educational institutions.